2020
DOI: 10.1186/s13690-020-00414-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in the pregnant women: an observational study in Shanghai, China

Abstract: Background Maternal vitamin D deficiency has been a worldwide concern in recent years. However the epidemiological data of vitamin D deficiency among large group of Chinese pregnant women is limited. This study is to evaluate the prevalence of vitamin D deficiency among pregnant women in Shanghai, China and to analyze the association of vitamin D status with some pregnancy outcomes (gestational diabetes and low birth weight). Methods A total of 34,417 pregnant women in Shanghai were included in this study fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…Our study found that the level of vitamin D of Chinese pregnant women in Shanghai was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) ng/ml, and 31.8% (303) pregnant women had severe vitamin D deficiency; 40.7% (388) had vitamin D deficiency; 25.1% (239) had vitamin D insufficiency; only 2.4% (23) had normal vitamin D; None were found to have vitamin D above 50 ng/ml. Our study found that the level of vitamin D increased with age groups (t = 8.5, p = 0.04); Vitamin D deficiency decreased with age groups (X 2 = 17.6, p = 0.04).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Our study found that the level of vitamin D of Chinese pregnant women in Shanghai was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) ng/ml, and 31.8% (303) pregnant women had severe vitamin D deficiency; 40.7% (388) had vitamin D deficiency; 25.1% (239) had vitamin D insufficiency; only 2.4% (23) had normal vitamin D; None were found to have vitamin D above 50 ng/ml. Our study found that the level of vitamin D increased with age groups (t = 8.5, p = 0.04); Vitamin D deficiency decreased with age groups (X 2 = 17.6, p = 0.04).…”
Section: Resultsmentioning
confidence: 56%
“…A few studies on vitamin D deficiency in Chinese pregnant women are after 20 weeks of pregnancy. Such as, the vitamin D deficiency rate (< 20 ng/ml) of pregnant women in Wuxi of China is 90% at 23–28 weeks of gestation [ 30 ], and the vitamin D deficiency rate (< 20 ng/ml) is 94.7% in Nanjing of China [ 31 ], and 90.2% in Beijing [ 21 ]. Our study population was a selected group of pregnant women who visited the outpatient clinic for their first prenatal examination when 12–14 weeks of gestation of Chinese pregnant women in Shanghai.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of vitamin D and the high prevalence of vitamin D deficiency, regular screening of vitamin D levels in autistic individuals and necessary intervention are recommended. Furthermore, pregnant and lactating women consume more vitamin D than usual and are generally deficient in vitamin D [ 66 ]; maternal and neonatal vitamin D status may be associated with subsequent diagnosis of ASD. Vitamin D status should be included in routine screening during pregnancy and lactation in order to provide appropriate clinical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Во всем мире существует проблема низкой информированности родителей о роли витамина D в организме, источниках его поступления, последствиях дефицита и организации профилактического приема препаратов витамина D. При этом лишь каждый 4-й ребенок в возрасте до 2 лет получает профилактическую дозу холекальциферола [17]. Большинство взрослых также не осведомлены и не принимают витамин D [18][19][20][21].…”
Section: таблица 5 уровень 25(он)d3 в плазме крови у детей в зависимости от сезона года и длительности инсоляции Table 5 Level 25(oh)d3 Dunclassified